Experimental infection of commercial layers using a Salmonella enterica sorovar Gallinarum strain: blood serum components and histopathological changes - Garcia, Kleber O.; Santana, André M.; Freitas Neto, Oliveiro C.; Simplício, Kalina M.M.G.; Alessi, Antonio C.; Berchieri Júnior, Ângelo; Fagliari, José J. (Brazilian Journal of Veterinary Pathology, 2010)
The purpose of the study was to evaluate the blood serum components and histopathological findings of commercial layers experimentally infected with Salmonella Gallinarum (SG), the microorganism responsible for the fowl typhoid. 180 commercial layers were distributed into three groups (G): G1 and G2 received 0.2mL of inoculum containing 3.3x108 and 3.3x105 CFU of resistant SG to the nalidix acid (Nalr)/mL, respectively, directly into their crops; G3 did not receive the inoculum (control group). The birds were inoculated when they were 5 days old and the euthanasia was performed 24 hours before and after infection and 3, 5, 7 and 10 days after the administration of the inoculum. In each day of collection, blood samples were obtained for biochemical tests of the blood serum besides macroscopic and histopathological examination of the birds. Data were submitted to analysis of variance by the SAS statistical program and the means were compared by Tukey´s test (P